Samartha darśana : lekhasanġraha (Prācārya Dāṇḍekara Dhārmika, Śaikshaṇika, va Sāṃskrtika Vāṅmaya Prakāśana Maṇḍala, 1982)
Contributed articles on the life, works, and teachings of Rāmadāsa, b. 1608, Hindu religious leder from Maharashrra.